2017
DOI: 10.1515/plua-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium sp. – a Potential Tool for Improving Protein Content in Peas and Faba Beans

Abstract: Abstract. Legume seed inoculation prior to sowing is a well-known practice in agriculture. Nitrogen fixation, due to the symbiotic relationship between legumes and rhizobia, improves the productivity of legumes. Rhizobia strain specificity can be observed very often, leading to differences in the total protein content. In this study two faba bean cultivars ('Karmazyn' and 'Bartek') and five pea cultivars ('Retrija', 'Zaiga', 'Lāsma', 'Vitra' and 'Bartek') were tested using various rhizobia strains. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…Faba bean varieties are therefore highly heterogeneous in size (less than 0.3 g to more than 1 g per seed) [71], color, and shape [80,81], depending on the cultivating area and the environmental conditions during the cropping year [82]. Soil composition, atmospheric nitrogen fixation efficiency, and environmental stress, such as drought, are all factors that can affect faba bean protein content [83,84]. Hood-Niefer, Warkentin, Chibbar, Vandenberg, and Tyler [42] have demonstrated that the protein content of 11 faba bean varieties grown in three western Canadian regions during two different years (2006 and 2007) fluctuated from 27.5 to 32.4%.…”
Section: Faba Bean Proteinsmentioning
confidence: 99%
“…Faba bean varieties are therefore highly heterogeneous in size (less than 0.3 g to more than 1 g per seed) [71], color, and shape [80,81], depending on the cultivating area and the environmental conditions during the cropping year [82]. Soil composition, atmospheric nitrogen fixation efficiency, and environmental stress, such as drought, are all factors that can affect faba bean protein content [83,84]. Hood-Niefer, Warkentin, Chibbar, Vandenberg, and Tyler [42] have demonstrated that the protein content of 11 faba bean varieties grown in three western Canadian regions during two different years (2006 and 2007) fluctuated from 27.5 to 32.4%.…”
Section: Faba Bean Proteinsmentioning
confidence: 99%